Heavy Metal Tolerance in Plants: Role of Transcriptomics, Proteomics, Metabolomics, and Ionomics - Singh, Samiksha; Parihar, Parul; Singh, Rachana; Singh, Vijay P.; Prasad, Sheo M. (Frontiers in Plant Science, 2016)
Heavy metal contamination of soil and water causing toxicity/stress has become one important constraint to crop productivity and quality. This situation has further worsened by the increasing population growth and inherent food demand. It have been reported in several studies that counterbalancing toxicity, due to heavy metal requires complex mechanisms at molecular, biochemical, physiological, cellular, tissue and whole plant level, which might manifest in terms of improved crop productivity. Recent advances in various disciplines of biological sciences such as metabolomics, transcriptomics, proteomics etc. have assisted in the characterization of metabolites, transcription factors, stress-inducible proteins involved in heavy metal tolerance, which in turn can be utilized for generating heavy metal tolerant crops. This review summarizes various tolerance strategies of plants under heavy metal toxicity, covering the role of metabolites (metabolomics), trace elements (ionomics), transcription factors (transcriptomics), various stress-inducible proteins (proteomics) as well as the role of plant hormones. We also provide a glance at strategies adopted by metal accumulating plants also known as “metallophytes”.